1984
DOI: 10.1149/1.2115916
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of As(III): I . Voltammetric Studies at Pt Electrodes in

Abstract: Hydrodynamic voltammetry and hydrodynamically modulated voltammetry at a disk electrode, and shielding experiments at a ring-disk electrode, were applied in a study of the electrochemical response of As (III). The adsorption of As(III) occurs at Pt electrodes with partial charge transfer. The adsorption isotherm was determined and a maximum coverage is established for CbAS(m~ > 6 X 10 ~M. The oxidation of As(III) is electrocatalyzed dramatically by formation of PtOH on the electrode, but is slow for a surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 23 publications
3
53
0
2
Order By: Relevance
“…Electrochemical deposition should be a promising and convenient method to remove the arsenic from aqueous solution and realize the recycling usage of leaching solution. A lot of efforts [2][3][4][5][6][7][8] have been done to investigate the electrochemical behavior of arsenic in aqueous solution, as well as the deposition rate and current efficiency of elementary As. It has been found that toxic gas arsine will be produced as by-product during the electrodeposition of elementary arsenic [9,10], which has become a very important issue for the study of arsenic deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical deposition should be a promising and convenient method to remove the arsenic from aqueous solution and realize the recycling usage of leaching solution. A lot of efforts [2][3][4][5][6][7][8] have been done to investigate the electrochemical behavior of arsenic in aqueous solution, as well as the deposition rate and current efficiency of elementary As. It has been found that toxic gas arsine will be produced as by-product during the electrodeposition of elementary arsenic [9,10], which has become a very important issue for the study of arsenic deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The curves indicate that there is direct proportionality between I −1 and ω −1/2 , and the intercept on I axes is not zero. A result can be drawn that a mixed control (ion transport and kinetics) was present in the reaction taking place at 0.84 V. 34,37 A curve has been drawn through the points obtained and the goodness of fit of each line is shown in Figure 4. Diffusion coefficient D has been calculated from the value of the slope using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…This peak correspond to the oxidation of As(III) to As(V) [39]. The reaction is likely electrocatalyzed by the formation of PtOH on the electrode [41,42]. The peak increased linearly with the addition of As(III) (Fig.…”
mentioning
confidence: 88%